Analisis Konjoin untuk Preferensi Konsumen Kemasan Produk Wedang Uwuh di P4S X Kabupaten Kulon Progo - Leony, Leony; Munambar, Siwitri; Aristi Rahayu, Novia (MASALIQ, 2025)
Wedang uwuh is a traditional herbal drink made from spices, valued for both its health benefits and cultural significance, and is currently marketed by MSMEs such as P4S X in Kulon Progo Regency. In product marketing, packaging serves as a crucial element influencing consumer appeal and purchasing decisions. This study aims to identify consumer preferences for wedang uwuh packaging design using conjoint analysis. A mixed-method approach was employed, involving 96 respondents aged 17–75 who were familiar with or had consumed wedang uwuh, selected through purposive sampling. Four packaging attributes were analyzed: product information, packaging shape, packaging color, and quantity. The analysis revealed that product information was the most influential attribute in determining consumer preferences, followed by packaging color, shape, and quantity. Consumers tended to prefer rectangular packaging, bright colors such as red, yellow, or blue, a content quantity of 10 pcs, and complete information including ingredients, consumption instructions, expiration date, net weight, and producer identity. These findings affirm that informative and visually appealing packaging design significantly influences consumer preferences. The practical implication of this study offers strategic recommendations for MSMEs to develop packaging designs that align with market demands, thereby enhancing the competitiveness of traditional herbal products at both local and national levels.